Microstructure, fractal geometry and corrosion properties of CrN thin films: The effect of shot number and angular position - Habibi, Maryam; Mirzaei, Saeed; Arman, Ali; Jurečka, Stanislav; Sadeghi, Mohammad; Zelati, Amir; Shakoury, Reza; Tanhaee, Ehsan; Ghobadi, Nader; Ehteram, Hamid; Ţălu, Ştefan (Materials today communications, 2022)
The effect of different plasma focus shots and angular positions (0° and 30°) on the properties of chromium nitride (CrN) coatings, deposited by a plasma focus (PF) device on stainless steel substrates, have been systematically investigated in this paper. The structural and morphological properties of CrN thin films were characterized by X-ray diffraction (XRD) and atomic force microscopy (AFM). Moreover, the corrosion behavior of the CrN thin films was investigated using the ‘c’ method. The XRD patterns demonstrated the growth of the polycrystalline structure composed of CrN/Cr2N nanograins and the enhanced crystallinity of the CrN coatings upon increasing the shot numbers. In addition, AFM results showed enhanced multifractal properties of the sample prepared at 0° angular position and a reducing trend in these properties for the layers prepared at 30° angular position. Moreover, they exhibited sharp hillock-like features on the surface, corresponding to the columnar growth of the CrN coatings, which further protruded as the number of shots increased. The results of the corrosion test showed that the resistance of stainless-steel substrate was improved by depositing the CrN coatings due to the formation of a passive and protective layer on its surface. Notably, ceramic CrN film, prepared through 10 shots at 30° angular position, showed the best corrosion resistance. Our strategy is advantageous for designing and manufacturing novel devices and instruments based on CrN corrosion resistant coating. [Display omitted] •CrN/SS films have been deposited at different plasma focus shots and angular positions by plasma focus (PF) instruments.•The effect of shot number and angular position on the surface microtexture, and corrosion features of the films was studied.•The 3-D surface analysis of the samples was performed using an atomic force microscope operating in tapping mode.